STUDY OF THE STATE OF THE HARD TISSUES OF THE TEETH IN CHILDREN AND IN CHILDREN WITH SENSORY DEPRIVATION OF VISION - Shpak, S.V.; Dienha, O.V.; Shnaider, S.A.; Pochtar, V.M.; Jenča, A.; Baleha, M.I.; Zhelizniak, N.A. (World of Medicine and Biology, 2023)
The study was devoted to studying the state of hard tissues of temporary and permanent teeth in children with sensory deprivation of vision. 116 blind children of different ages took part in the research. Children were divided by age into two groups – 6–8 years old (61 children) and 11–14 years old (56 children). All children underwent a comprehensive examination of the main disease and dental status according to a single scheme. The dental examination was carried out in a dental office. As a result of the conducted research, it was established that the obtained data are proof of the increased intensity of caries in children with blindness. These data are the basis for the development and implementation of a medical and preventive complex aimed at helping the children of this contingent.